Spondilitis Tuberkulosis: Sebuah Laporan Kasus - Rifka Putri Dewi; Fitriyani Fitriyani (CV. Jasa Sukses Abadi, 2026)
Tuberculous spondylitis is the most common form of musculoskeletal tuberculosis, accounting for approximately 40–50% of all musculoskeletal tuberculosis cases. The disease may lead to vertebral body destruction, kyphotic deformity, paravertebral abscess formation, and neurological deficits resulting from spinal cord compression. Diagnosis is often delayed because the initial manifestations are nonspecific and may occur in the absence of classic constitutional symptoms such as fever, chronic cough, weight loss, or night sweats. This case report aims to highlight the importance of magnetic resonance imaging (MRI) in establishing the diagnosis of tuberculous spondylitis in a patient presenting primarily with neurological manifestations without systemic symptoms. A 44-year-old man presented with numbness and a burning sensation in the left chest for 20 days, accompanied by a progressive thoracolumbar gibbus deformity that had developed over one year. Neurological examination revealed left lower extremity weakness with a motor strength grade of 3/5. The patient denied fever, chronic cough, weight loss, night sweats, or a history of tuberculosis contact. Laboratory investigations demonstrated an elevated erythrocyte sedimentation rate, while chest radiography was unremarkable. Thoracic MRI revealed multiple compression fractures involving the T6–T8 vertebrae, bone marrow edema, bilateral epidural and paravertebral abscesses, and intradiscal fluid at the T7–T8 level, findings highly suggestive of tuberculous spondylitis. The patient was scheduled for surgical decompression followed by long-term anti-tuberculosis therapy. This case highlights that tuberculous spondylitis may present predominantly with progressive neurological deficits despite the absence of constitutional symptoms and normal chest radiographic findings. Early MRI evaluation plays a crucial role in prompt diagnosis and timely management, thereby preventing irreversible neurological complications.